Revision periarterial sympathectomy for recurrent digital ischaemia: a report with 11 patients. (October 2021) - Rudolph, Megan; Butler, Katherine; Prabhu, Shamit; Browne, Donald; Koman, L. Andrew; Li, Zhongyu
Following periarterial sympathectomy, patients with recurrent digital ischemia due to vasospastic or vaso-occlusive disease have few remaining treatment options. We performed a retrospective review from 1997 to 2019 to determine the safety and efficacy of revision periarterial sympathectomy. Eleven patients were identified who underwent revision periarterial sympathectomy, performed on average 84 months after their initial procedure. Preoperatively, all patients had worsening ischemic pain and five had non-healing digital ulcers. Revision digital periarterial sympathectomy alone was performed in seven patients, while four had a more extensive sympathectomy. Mean follow-up after revision was 23 months (range 3 to 76). Eight patients had symptomatic improvement and four healed their digital ulcers. Three patients developed new ulcers during follow-up, of which two healed with conservative management and one required three digital amputations. Revision periarterial sympathectomy is effective in providing symptomatic improvement and digital ulcer healing with minimal postoperative complications. Level of evidence: IV